Circularly polarised loop‐type ground radiation antenna for mobile devices using a resonance inductor and capacitor. Issue 5 (1st March 2018) - Zahid, Z.; Qu, L.; Kim, H.H.; Kim, H.
Abstract : In this Letter, a circularly polarised loop‐type ground radiation antenna has been proposed for internet of things (IoT) applications that use a combination of an inductor and a capacitor in the resonance loop. The antenna has been designed within a 7 mm × 7 mm clearance near the left corner of a 60 mm × 30 mm ground plane. The resonance capacitor is placed at the corner of the radiating loop of the antenna to excite two orthogonal modes on the ground plane. The authors propose that the polarisation of the antenna can be controlled by varying the inductances of the sections of the radiating loop of the antenna. Employing this approach, an inductor is used at the left section of the radiating loop to control the phase difference of the orthogonal modes. Implementing the proposed design, the measured axial ratio bandwidth with reference to 3 dB was 300 MHz, and the matching bandwidth with reference to −6 dB was 110 MHz.